A simple mechanism for mid-crustal shear zones to record surface-derived fluid signatures - Raimondo, T.; Clark, Christopher; Hand, M.; Cliff, J.; Anczkiewicz, R. (Geological Society of America, 2013)
Ion microprobe analyses of garnet porphyroblasts from three separate splays of the mid-crustal Walter-Outalpa shear zone, Curnamona Province, South Australia, indicate homogeneous δ18O values of <3‰. Integrated Lu-Hf geochronology and electron microprobe compositional mapping demonstrate that closed-system growth of these isotopically light garnets initiated as early as 531 Ma, prior to peak metamorphism and deformation during the Delamerian Orogeny (514–490 Ma). We attribute this to the prograde burial and dehydration of altered fault panels under thick sedimentary sequences during pre-orogenic basin formation. Contrary to established fluid transport models, surficial fluid signatures were not imposed at depth by large fluxes of downward-penetrating fluids, but rather by the exposure and meteoric alteration of fault rocks that were subsequently buried and reactivated as ductile shear zones. The existence of low δ18O values in deeply exhumed shear zones may therefore be indicative of fault structures that have a prior history of surface exposure, weathering, burial and re-exposure.